Systematic review with meta-analyses: does the pathogen matter in post-infectious irritable bowel syndrome?. (4th May 2019) - Svendsen, Anna Tølbøll; Bytzer, Peter; Engsbro, Anne Line
Abstract: Objective: Acute gastroenteritis (AGE) is a risk factor for post-infectious irritable bowel syndrome (PI-IBS). This systematic review evaluates the prevalence and risk-factors of PI-IBS after AGE by specific pathogens. Materials and methods: Medline (1966–2019) and Embase (1974–2019) were searched for studies evaluating PI-IBS minimum 3 months after AGE with Campylobacter spp., Salmonella spp., Shigella spp., Escherischia coli, Clostridium difficile, norovirus, rotavirus, Cryptosporidium spp. or Giardia intestinalis using validated criteria for IBS. Pooled prevalence (PP), odds ratios (OR) and risk factors were determined for single pathogens, groups of bacteria, viruses and parasites, and overall for AGE caused by any pathogen. Random-effect models were used for meta-analyses. Results: A total of 34 articles were included. PP of PI-IBS after Campylobacter spp. was 12% (confidence interval 95% [CI]: 10–15%), Salmonellosis 12% (CI: 9–15%), Shigellosis 11% (CI: 8–15%), C. difficile 14% (CI: 4–29%) and E. coli spp. 12% (CI: 5–20%). OR of PI-IBS after salmonellosis was 5.5 (CI: 2.3–12.8) and after shigellosis 13.8 (CI: 4.2–45.4). Bacterial AGE overall showed OR 5.8 (CI: 4.0–8.3) and AGE caused by any pathogen OR 4.9 (CI: 3.9–6.1). Few studies exist on viral and parasitic gastroenteritis. Conclusions: Current literature show similar risks for bacterial pathogens. Studies are limited for viral and parasitic pathogens. The evaluated risk-factors for PI-IBS varied among the included studies and the existing evidence is insufficient to identify pathogen-specific risk factors.